1991
DOI: 10.1002/hed.2880130404
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the tonsillar fossa: A nonrandomized comparison of irradiation alone or combined with surgery: Long‐term results

Abstract: The results of therapy are reported in 296 patients with histologically proven epidermoid carcinoma of the tonsillar fossa; 127 were treated with irradiation alone (5,500 to 7,000 cGy), 133 with preoperative radiotherapy (2,000 to 3,000 cGy) or were initially planned for preoperative irradiation but treated with radiotherapy alone, and 36 with postoperative irradiation (5,000 to 6,000 cGy). The operation in all but 4 patients consisted of an en bloc radical tonsillectomy with ipsilateral lymph node dissection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
3

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 33 publications
1
14
0
3
Order By: Relevance
“…The data show that survival depends essentially on the primary control of the tumour in the T position (17,18). Salvage procedures have some effect, as 48% (28:58) of the patients who had attempted curative salvage treatment were controlled, but this is still only a small proportion, 34% (58:173), of the patients with recurrence who can have a curative salvage attempt.…”
Section: Discussionmentioning
confidence: 99%
“…The data show that survival depends essentially on the primary control of the tumour in the T position (17,18). Salvage procedures have some effect, as 48% (28:58) of the patients who had attempted curative salvage treatment were controlled, but this is still only a small proportion, 34% (58:173), of the patients with recurrence who can have a curative salvage attempt.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] There are no dedicated randomized trials that have focused on comparing radiotherapy versus surgery for oropharyngeal carcinoma. Radiotherapy is preferred at many centers because of presumed lower morbidity and better functional and cosmetic outcome compared with surgical treatment, particularly with the increased use of chemoradiation.…”
mentioning
confidence: 99%
“…Other investigators have reported that complications of RT, in particular dysphagia, may be just as severe as that expected from extirpative surgery. 6,10 Since 1993, we have prospectively assessed the QOL of all head and neck cancer patients treated at the University of Washington (UW) by administering the UW QOL questionnaire both before and after treatment. 11 The purpose of this pilot study was to assess the QOL of patients with advanced oropharyngeal cancer who had been successfully treated (ie, without evidence of disease at 1 year) by primary RT or by primary surgical resection and postoperative RT.…”
mentioning
confidence: 99%